Microtubule nucleation: the waltz between γ-tubulin ring complex and associated proteins - Liu, Peng; Würtz, Martin; Župa, Erik; Pfeffer, Stefan; Schiebel, Elmar (Current opinion in cell biology, 2021)
Microtubules are essential cytoskeletal elements assembled from αβ-tubulin dimers. In high eukaryotes, microtubule nucleation, the de novo assembly of a microtubule from its minus end, is initiated by the γ-tubulin ring complex (γ-TuRC). Despite many years of research, the structural and mechanistic principles of the microtubule nucleation machinery remained poorly understood. Only recently, cryoelectron microscopy studies uncovered the molecular organization and potential activation mechanisms of γ-TuRC. In vitro assays further deciphered the spatial and temporal cooperation between γ-TuRC and additional factors, for example, the augmin complex, the phase separation protein TPX2, and the microtubule polymerase XMAP215. These breakthroughs deepen our understanding of microtubule nucleation mechanisms and will link the assembly of individual microtubules to the organization of cellular microtubule networks.
Available online: 12 November 2020
Gesehen am 14.04.2021